INTEGRATED TEACHING FOR SUSTAINABLE DEVELOPMENT: BEHAVIORAL CHANGES IN STUDENTS - Alma ŠKUGOR; Ana ŠKARO; Ines NOVAK (International Journal of Social and Educational Innovation)
Achieving behavioral changes and acquiring new skills necessitates a multilevel approach, beginning at the individual level and extending to local and global contexts. Teachers hold a pivotal role in fostering a sustainability-oriented society by preparing students to become active citizens equipped with knowledge, competencies, and skills, while demonstrating entrepreneurial and proactive behavior. This study aims to examine the behavioral changes observed in students following the implementation of a project that integrated media-based educational content and didactically structured materials on sustainable development. The project was conducted between November 2021 and June 2022, involving 41 schools across Croatia. A total of 69 teachers and 1,037 first- and second-grade primary school students participated in the project activities. Data collection tools included an activity log, an activity recording table, a Facebook support group for teachers, and a final evaluation in the form of an online questionnaire featuring reflections from both teachers and students. These paper presents the findings of the final evaluation focused on students, analysed through descriptive statistical methods and qualitative approaches. Teachers observed diverse changes in student behavior, including increased care for plants and animals, maintaining cleanliness in their surroundings, valuing a healthy diet, respecting cultural and natural heritage, and heightened motivation for independent exploration. Additional improvements included enhanced empathy, collaboration, peaceful conflict resolution, polite behavior, inclusivity, self-confidence, freedom of expression, and active participation in discussions.